Designing mathematical modeling process worksheets for unifying assessment, instruction, and learning - Bambang Riyanto (Inovasi Kurikulum, 2024)
The importance of unifying assessment is because current assessment practices are cumulative products of learning theories and measurement models developed to meet social and educational needs at different times. The research aims to produce a valid mathematical model for unifying assessment, instruction, and learning. The research approach is development research, which consists of 3 steps: analysis, design, and evaluation. The analysis step applies student analysis, curriculum, mathematical modeling, and real-world problems. The second step is design and product. In the final step, researchers used a formative evaluation design consisting of self-evaluation, one-to-one, expert review, small group, and field tests. Data were analyzed using descriptive analysis methods: (1) walk-through, analysis based on expert opinions to obtain a valid mathematical modeling process to unify assessment, instruction, and learning; (2) Results Analysis of the one-to-one. Expert validation of mathematical modeling processes in process worksheets can unify assessment, instruction, and learning. One-to-one results are exciting, challenging, and novel. A mathematical modeling process device was obtained as a valid process worksheet for unifying assessment, instruction, and learning. It is necessary to research other subjects using volatility, uncertainty, complexity, and ambiguity in real-world contexts.   Abstrak Pentingnya penyatuan asesmen, karena praktik asesmen yang ada saat ini merupakan produk kumulatif dari teori belajar dan model pengukuran yang dikembangkan untuk memenuhi kebutuhan sosial dan pendidikan pada waktu yang berbeda. Tujuan penelitian adalah menghasilkan instruksi pemodelan matematika yang valid untuk penyatuan penilaian, instruksi dan pembelajaran. Pendekatan riset adalah Development research yang terdiri dari 3 langkah yaitu analisis, desain dan evaluasi. Pada langkah analisis diterapkan analisis siswa, kurikulum, pemodelan matematika dan permasalahan dunia nyata. Langkah kedua, desain dan produk. Pada langkah terakhir, peneliti menggunakan desain evaluasi formatif yang terdiri dari evaluasi diri, one-to-one, expert review, small group, dan field test. Data dianalisis dengan menggunakan metode analisis deskriptif: (1) walk through, analisis berdasarkan komentar para ahli untuk memperoleh instruksi pemodelan matematika yang valid untuk menyatukan penilaian, instruksi dan pembelajaran; (2) Menganalisis hasil one-to-one review. Validasi ahli instruksi pemodelan matematika dalam bentuk lembar kerja proses dapat menyatukan penilaian, instruksi dan pembelajaran. Hasil one-to-one masalah pemodelan ini menarik dan menantang serta baru. Diperoleh perangkat instruksi pemodelan matematika berupa lembar kerja proses yang valid untuk penyatuan penilaian, instruksi dan pembelajaran. Perlu dilakukan penelitian pada mata pelajaran lain dengan menggunakan konteks dunia nyata yang volatilitas, ketidakpastian, kompleksitas dan ambiguitas. Kata Kunci: asesmen; instruksi; lembar kerja proses; pembelajaran; pemodelan matematika; pendesainan